2022
DOI: 10.1111/adb.13152
|View full text |Cite
|
Sign up to set email alerts
|

"It's a beer!": Brain functional hyperconnectivity during processing of alcohol‐related images in young binge drinkers

Abstract: Alcohol attentional bias has been pointed as a major marker of alcohol misuse.Recent evidence has revealed that brain functional connectivity (FC) may be a valuable index of the brain networks' integrity in young binge drinkers (BDs). However, there is no study to date examining the FC networks linked to the processing of alcohol-related images in this population. The present study aimed to explore the FC signatures underlying alcohol attention bias in young BDs. Thus, electroencephalographic (EEG) activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
(151 reference statements)
1
10
0
Order By: Relevance
“…In particular, beta reflects a top-down “status quo” signal maintaining endogenous rules or long-term “priors” regarding environmental stimuli and behaviors involved with binding of large scale sensorimotor networks (Engel and Fries, 2010 ; Spitzer and Haegens, 2017 ; Betti et al, 2021 ; Michail et al, 2022 ). There is also strong evidence for beta’s role in the genetic risk for AUD (Porjesz et al, 2002 ; Smit et al, 2018 ), binge drinking (Lees et al, 2019 ; Almeida-Antunes et al, 2022 ), and also in drug craving, e.g., in AUD (Huang et al, 2018 ) and MUD (Zhao D. et al, 2021 ), an important factor related to relapse (Serre et al, 2018 ; Stohs et al, 2019 ). Overall, dysregulated beta in SUD and its modification by abstinence or treatment, and its association with a range of neurocognitive processes, suggests that higher beta may serve as a marker of neurobehavioral deficits in motor and executive control, impulsivity, and endogenously-driven habits in SUD.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, beta reflects a top-down “status quo” signal maintaining endogenous rules or long-term “priors” regarding environmental stimuli and behaviors involved with binding of large scale sensorimotor networks (Engel and Fries, 2010 ; Spitzer and Haegens, 2017 ; Betti et al, 2021 ; Michail et al, 2022 ). There is also strong evidence for beta’s role in the genetic risk for AUD (Porjesz et al, 2002 ; Smit et al, 2018 ), binge drinking (Lees et al, 2019 ; Almeida-Antunes et al, 2022 ), and also in drug craving, e.g., in AUD (Huang et al, 2018 ) and MUD (Zhao D. et al, 2021 ), an important factor related to relapse (Serre et al, 2018 ; Stohs et al, 2019 ). Overall, dysregulated beta in SUD and its modification by abstinence or treatment, and its association with a range of neurocognitive processes, suggests that higher beta may serve as a marker of neurobehavioral deficits in motor and executive control, impulsivity, and endogenously-driven habits in SUD.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using neuroimaging and electroencephalography (EEG) techniques have also revealed abnormalities in the neural correlates of attention and executive functioning related to BD ( Crego et al, 2012 ; Campanella et al, 2013 ; López-Caneda et al, 2013 ). Also, evidence from neurofunctional studies showed increased neural reactivity for alcohol-related information in young BDs ( Petit et al, 2013 , 2014 ; Brumback et al, 2015 ; Ryerson et al, 2017 ; Almeida-Antunes et al, 2022 ). The altered inhibitory control together with the augmented reactivity to alcoholic stimuli in BDs may constitute a risk factor for the development of alcohol dependence, since it may result in automatic action-tendencies to approach alcohol and difficulties to control alcohol intake ( Peeters et al, 2012 ; Lannoy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… 1 Such a pattern of alcohol misuse is particularly hazardous during adolescent neurodevelopment. 2 , 3 It causes substantial alterations in the brain's integrity, for example, in structural 4 , 5 and functional aspects, 6 , 7 , 8 , 9 as well as neuropsychological alterations, 10 and could also increase psychological traits such impulsivity and disinhibited sensation seeking. 10 …”
Section: Introductionmentioning
confidence: 99%